Yatarak fizyoterapi alan hastaların yaşam kaliteleri ve maliyet analizi - (:unkn) unknown (My University, 2013)
Amaç: Lokomotor sistem sorunları nedeniyle yatarak fizyoterapi alan hastaların yaşam kaliteleri ve maliyet analizlerini ortaya koymaktır. Hastalar ve Yöntem: Yatarak fizyoterapi alan olguların demografik verileri kaydedildi ve 15 D yaşam kalite sorgulaması yapıldı. Maliyetleri hesaplandı. Yaşam kalitesi ölçeği verilerini kullanarak hesaplanan, kaliteye ayarlanmış yaşam yılı (KAYY) sayısını kullanarak ekonomik analiz yapılmıştır. Bulgular: Doksan üç olgunun 75i (%80,64) kadın, 18i (%19,35) erkek ve yaş ortalaması 61,45±14,52 idi. Gonartroz, hemipleji, lomber disk herni, Gullian Barre sendromu, omuzun sıkışma sendromu, lomber spondiloz, servikal disk hernisi olan hastaların yaşam kalitesi diğer gruplara göre anlamlı düzeyde düşük bulunmuştur (F=5,89; p<0,05). Gonartroz, hemipleji, lomber disk herni gruplarında tedavi için yapılan harcamalar yaşam kalitesini anlamlı düzeyde artırmaktadır (F=34,12; p<0,05). Sonuç: Gonartroz, hemipleji, lomber disk hernisi, yaşam kalitesini en çok bozan hastalıklardır. Bu hastalıklarda tedavi için yapılan harcalamalar yaşam kalitelerini anlamlı düzeyde arttırmaktadır.

Objectives: To reveal the quality of life of hospitalized patients with problems of the locomotor system who have received physical therapy, and provide a cost analysis. Patients and Method: Demographic data were recorded for patients who received physical therapy. Health-related quality of life (HRQoL) was assessed by 15-dimensional standardized instrument (15D). The cost was calculated. An economic analysis was made to consider data from HRQoL and quality adjusted life year (QALY) scales. Result: Of ninety three patients, 75 were female (80.64%), 18 were male (19.35%) and the average age was 61.45±14.52. The quality of life was low for the patients with gonarthrosis, hemiplegia, lumbar disc herniation, Guillain- Barré syndrome, subacromial impingement syndrome, lumbar spondylosis, cervical disc herniation when compared with the patients with other locomotor system problems treated by physical therapy (F=5.89; p<0.05). The expenses for the treatment of selected diagnosis patients such as gonarthrosis, hemiplegia, lumbar disc herniation significantly increased the quality of life of these patients (F=34.12; p<0.05). Conclusion: Lumbar disc herniation, gonarthrosis and lumbar spondylosis are the diseases, that reduced the quality of life the most. The costs incurred for the treatment of these diseases, significantly increased the quality of life of these patients.There was no statistically significant difference neither in the quality of life of other patients that had hemiplegia, Guillain-Barré syndrome, subacromial impingement syndrome, cervical disc herniation, nor in the expenses for the treatment of these patients.
Quality of life and cost analysis of hospitalized patients receiving physical therapy
Keywords: Geriatri ve Gerontoloji